The use of Facebook in marketing communication by local tourist organizations in Poland - Korbiel, Karolina (Turyzm/Tourism, 2021)
The aim of the article is to show to what extent local tourist organizations in Poland use their Facebook accounts for marketing communication. 84 out of 121 on the list published on the Polish Tourist Organization website participated in the study which was carried out using a diagnostic survey method. The results show that Facebook profiles are largely not run in accordance with the guidelines formulated in the literature and many organizations do not have their own account at all. Representatives of organizations declare that they are aware of the need for the greater involvement of social media in promotional activities but find such obstacles as a lack of financial resources and a lack of personnel who could professionally run them.